Antimicrobial and Antioxidant activity of leaf and flower extract of Caesalpinia pulcherrima, Delonix regia and Peltaphorum ferrugineum - Vivek M.N, Sachidananda Swamy H.C, Manasa M, Pallavi S, Yashoda Kambar, Asha M.M, Chaithra M, Prashith Kekuda T.R, Mallikarjun N, Onkarappa R (Journal of Applied Pharmaceutical Science, 2013)
The present study was undertaken to determine antimicrobial and antioxidant activities of leaf and flower extracts of Caesalpinia pulcherrima, Delonix regia and Peltaphorum ferrugineum. Antimicrobial activity was tested against Staphylococcus aureus, Salmonella typhi, Candida albicans and Cryptococcus neoformans by Agar well diffusion assay. Antioxidant activity was determined by DPPH free radical scavenging assay, ABTS free radical scavenging assay, Ferric reducing assay and Total antioxidant capacity determination. Total phenolic content of extracts was estimated by Folin-Ciocalteau Reagent method. S. typhi and C. neoformans were susceptible to extracts to greater extent than S. aureus and C. albicans among bacteria and fungi respectively. Except C. pulcherrima extract, the leaf extracts were more effective in inhibiting bacteria than flower extracts. Leaf extracts have shown high antifungal activity than flower extracts. The extracts have shown dose dependent scavenging of DPPH and ABTS radicals. Scavenging of ABTS radicals was more efficient than that of DPPH radicals as revealed by low IC50 values. All leaf extracts except C. pulcherrima displayed stronger scavenging activities than flower extracts. Similar results were observed in ferric reducing assay and total antioxidant capacity determination. Total phenolic content was found to be higher in leaf extracts (except C. pulcherrima) than flower extracts. A correlation has been observed between phenolic content of leaf and flower extracts and the antioxidant activity. A marked antimicrobial and antioxidant activity of leaf and flower extracts was observed which may be attributed to the presence of phenolic compounds and other phytochemicals. The plants can be used to control infectious diseases and oxidative damage.
Keywords: Caesalpinia pulcherrima, Delonix regia, Pel